"Paired competition": A new mechanism for the innovation of urban grassroots governance. (January 2023) - Huang, Xiaochun; Zhou, Li-An
In recent years, the focus of urban grassroots governance in China has experienced a fundamental change in direction from economic growth to public service and social management. Economic growth can be easily quantified, while public service and social management cannot, thus performance evaluation is largely dependent on "impression-based results". Under such circumstances, a new mechanism of "paired competition" has been put in place to pair superior vertical lines of authority ( tiao ) with subordinate horizontal levels of grassroots governments ( kuai ) on a voluntary basis. Pairs compete with other pairs in areas of public services and social management. Paired competition can facilitate close cooperation between the tiao side and the kuai side, promote innovation, and generate quick "impression-based results". However, the mechanism also generates negative incentives, which lead to excessive innovation and the reluctance to adopt good practices on the part of rival pairings. The case study detailed here is that of a "community analysis tool" promoted by the civil affairs bureau of "district A" in a major Chinese city. In addition to examining the organizational and operational logic of "paired competition", this study also compared "paired competition" with the traditional methods of the "promotion tournament competition" and "special-purpose project system".